1979
DOI: 10.1111/j.1748-1716.1979.tb06372.x
|View full text |Cite
|
Sign up to set email alerts
|

Renin, aldosterone and Cortisol during ethanol intoxication and hangover

Abstract: The effect of ethanol intoxication and hangover on plasma renin activity (PRA), plasma aldosterone (PA) and plasma cortisol (PC) concentrations was studied in 7 healthy supine men in controlled clinical conditions during 18 h beginning at 6 p.m. Large individual variation was observed in the response of PRA, PA and PC to ethanol. Following ethanol, stimulation of PRA was observed at the 14th and the 16th hour (P less than 0.05), of PA at the 4th and the 6th hour (P less than 0.01 and P less than 0.05, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 30 publications
(31 reference statements)
3
27
1
Order By: Relevance
“…Urinary excretion of epinephrine is greater during withdrawal than during alcohol administration," and plasma norepinephrine levels are highest 13 to 24 hours after alcohol cessation." In addition, plasma arginine vasopressin" and plasma renin activity 37 are increased during the withdrawal phase. Whether the effect on BP begins during the alcohol intoxication or withdrawal period is of more physiologic than clinical interest, since either way the effect is due to alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary excretion of epinephrine is greater during withdrawal than during alcohol administration," and plasma norepinephrine levels are highest 13 to 24 hours after alcohol cessation." In addition, plasma arginine vasopressin" and plasma renin activity 37 are increased during the withdrawal phase. Whether the effect on BP begins during the alcohol intoxication or withdrawal period is of more physiologic than clinical interest, since either way the effect is due to alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Gill et al 33 noted similar changes in urea and suggested that the alcohol-induced diuresis may have led to increased urea clearance. Linkola et al 34 noted an initial suppression of plasma renin activity following alcohol ingestion and found that plasma renin activity rose only during the hangover period. Changes in the renin-angiotensin-aldosterone axis do not appear to account for the rise in blood pressure with alcohol ingestion.…”
Section: Figure 3 Effect Of Alcohol (*) and Placebo (O) On Plasma Nomentioning
confidence: 99%
“…A similar fall has been noted by other workers, and levels usually do not rise until the withdrawal period. 34 The acute, alcohol-induced elevations of plasma cortisol have been reported to be related to the degree of discomfort and usually are not encountered with blood alcohol levels below 100 mg/dl.…”
Section: Figure 3 Effect Of Alcohol (*) and Placebo (O) On Plasma Nomentioning
confidence: 99%
“…Several socio-economic factors for each prefecture were used in a stepwise multiple regression analysis. These factors were, the annual income per capita, the number of men per 100,000 who are receiving public aid, the number of tatamis (a Japanese traditional floor unit) per household, the unemployment rate per 100,000 men, the unmarried rate per 100 men aged [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Age-adjusted stroke mortalities for all ages and for the middle-aged by sex, and the male:female ratio of age-adjusted stroke mortality for the middle-aged and all ages were used as dependent variables, while alcohol consumption, salt intake and socio-economic factors were used as independent variables in a stepwise multiple regression analysis. The same independent variables were used for the stepwise multiple regres- Table 1 shows the mean and standard deviations of the variables used in this study.…”
Section: Statistics For 46 Prefectures Excluding Okinawa Inmentioning
confidence: 99%